Prospective Randomized Trial of Rotor Ablation vs Conventional Ablation for Persistent Atrial Fibrillation: REAFFIRM Trial - Johannes Brachmann; Thomas Vogtmann; John Hummel; Vijay Swarup; David Wilber; Joshua Rapkin; Shlomo Shpun; Anne Sarver; Tamás Szili‐Törok (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Pulmonary vein isolation (PVI) is the cornerstone therapy for symptomatic drug‐refractory atrial fibrillation yet is not curative in a large segment of patients. Focal and rotational drivers are proposed to be involved in atrial fibrillation mechanisms but their ablation has produced variable outcomes. REAFFIRM (The Randomized Evaluation of Atrial Fibrillation Treatment with Focal Impulse and Rotor Modulation Guided Procedures) trial (NCT‐02274857) objective was to compare the safety and effectiveness of conventional ablation with and without Focal Impulse and Rotor Modulated (FIRM) ablation, guided by global basket mapping, for the treatment of persistent atrial fibrillation. Methods Three hundred seventy‐five patients were enrolled and randomized at 18 centers. The Intent‐to‐Treat population consisted of 350 patients (171 FIRM, 179 Conventional). Primary effectiveness was defined as single procedure freedom from atrial fibrillation/atrial tachycardia recurrence at 3 to 12 months post index procedure. Results Three hundred twenty‐four patients completed the 12‐month follow‐up. Patients in the FIRM arm had a larger left atrium (P <0.01). Primary effectiveness at 3 to 12 months was 69.3% in FIRM and 67.5% in Conventional (NS), with no difference in ablation procedure time or safety. A subset of patients (41% FIRM, 49% Conventional) received extra ablation. Primary effectiveness in the on‐treatment subgroups was 65% PVI‐only, 69.6% PVI +extra, 77.7% FIRM+ PVI‐only, and 57.7% FIRM+ PVI +extra (P=0.09). Conclusions Intention‐to‐treat analysis failed to provide evidence for the superiority of adding ablation of focal or rotational sites to conventional ablation. Registration URL: https://clinicaltrials.gov; Unique Identifier: NCT‐02274857.